Faktor-Faktor yang Mempengaruhi Struktur Modal pada Perusahaan Manufaktur yang Terdaftar Di Bursa Efek Indonesia (BEI) Periode 2012-2016 (Studi Kasus pada Sektor Food and Beverage) - Cyntia Caroline DS; Sri Hasnawati; Prakarsa Panjinegara (E-journal Field of Economics, Business and Entrepreneurship (EFEBE), 2022)
Capital structure is an equalization beetwen the use of own capital and the use of loan, it means how much the own capital and how much the loan that will be used can produce an optimal capital structure. Considering the amount of influencial factors to the growth of assets, firm size, profitability and liquidity to capital struture of manufacture company in food and beverage product sector. The aim of this research is to know and to evaluate the influence between the growth of assets, firm size, profitability and likuidity to manufacture company capital struture in food and beverage product sector which listed in Indonesian Stock Exchange in 2012-2016 period. The population of the research is food and beverage companies listed in Indonesia Stock Exchange 2012-2016. Based on purposive sampling get 14 companies for the samples. The analysis tool used is multiple linear regression analysis. Before analyzing the multiple linear regression has been to test the assumption of normality and test Classical to the sample data. The results of research are growth, size have significant positive effect on the capital structure,profitability asset has significant negative effect on capital structure, and the liquidity does not significantly affect the company's capital structure.